Variasi Heat Recovery Time Terhadap Unjuk Kerja Chiller Sistem Adsorpsi 2 BED Pada Temperatur Desorpsi 700C - Tomi Sinaga; Awaludin Martin; Nasruddin Nasruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Adsorption cooling system double bed with silica gel as adsorbent and water as the adsorbate is expected to reduce the use of refrigerant in the vapor compression system that utilizes refrigerant chlorofluorocarbon (CFC) and hydrochlorofluorocarbon (HCFC) that could potentially damage the ozone layer and increase global warming. This study aims to increase the value of the COP (Coeficient Of Performance) and SCP (Specific Cooling Power) adsorption cooling system double bed by testing. The method in this research is by means of heat and mass recovery time of the system. Methods of heat recovery time is done to improve the performance of adsorption double bed system-water pair silica gel as adsorbent-adsorbate. Based on test data and calculations are obtained, the lowest temperature of the water coming out of the evaporator is 12.57 0C with a change in average highest temperature was 2.440C. The highest COP value of the adsorption cooling system amounted to 0.49 in heat hecovery time 40 s and cycle time 500 s.Keywords: adsorption, heat recovery, cooling system, silica gel.